EFL Classroom Interaction through Contextual Teaching and Learning: A Qualitative Study - ribahan ribahan (EDULANGUE, 2023)
Contextual teaching and learning (CTL) and classroom interaction are closely intertwined and have a significant influence on each other. The latter enables students to ask questions, seek clarifications, and receive immediate feedback. This qualitative research aimed to explore classroom interaction and the various patterns of interaction among students in an English as a Foreign Language (EFL) class using CTL as the teaching approach. Data were collected through observations, video recordings, and questionnaires, which were then analyzed using a series of stages, namely data reduction, data display, categorization, and drawing conclusion. The findings revealed that classroom interaction occurred in three phases: pre, whilst, and post-activities. The study also unveiled three types of interaction patterns, namely clarification requests, mime, and confirmation checks. The percentage of interaction between the teacher and students was 94.28%; between students and the teacher was 82.85%; and between students themselves was 88.57%. The most common interaction patterns were clarification requests (80%), mime (71.42%), and confirmation checks (65.71%). These results indicate that the teacher effectively implemented CTL in the EFL teaching and learning process, fostering active and communicative engagement between the teacher and students. Future researchers are encouraged to explore the implementation of CTL components in classroom interactions within English language teaching activities